Observable Effects of Atmospheric Pollution on Outpatient and Inpatient Morbidity in Bulgaria - Мagdalena PLATIKANOVA; Mariana PENKOVA-RADICHEVA (Tehran University of Medical Sciences, 2016)
Background: One of Europe's most well-developed industrial regions is found in the Republic of Bulgaria. The industrialization of the region has a big impact on air pollution. Thermal power plant "Maritza East" (the largest of its kind in southeastern Europe), the army training range, machine manufacturers, household heating and high volume of automobile traffic are all major sources of pollution in the region. Methods: A five year study (2009-2013) followed yearly concentrations of principal atmospheric pollutants such as sulfur dioxide, dust, nitrogen dioxide, lead aerosols and hydrogen sulfide, and the way in which those levels had an effect on morbidity (outpatient and inpatient medical care) in the area. Statistical processing of data has been completed to represent and analyze the collected data in nonparametric and alternative format. Results: Atmospheric pollution affects human health directly through pathological changes in the human organism. The registered outpatient care provided for the period 2009-2013 is highest for diseases of the cardiovascular system (11.85%), the respiratory system (17.34%) and the genitourinary system (9.76%). The registered rate of hospitalization for the same period is for diseases of the digestive system (11.90%), the cardiovascular system (11.85%), respiratory system (10.86%) and the genitourinary system (8.88%). Conclusion: The observed period shows a decrease in average yearly concentrations of the principal atmospheric pollutants in the industrial region (Bulgaria) and reflects a decrease in morbidity based on outpatient care and an increase in morbidity by inpatient care (hospitalization). Our findings should be corroborated in future longitudinal studies.   Keywords: Atmospheric pollution, Morbidity, Industrial region, Bulgaria